Social determinants of seeking emergency and routine dental care in Saudi Arabia during the COVID-19 pandemic - Dalia E. Meisha; Ahad Mosallem Alsolami; Ghaliah Muslih Alharbi (BMC, 2021)
Abstract Background Between March and June 2020, closing dental clinics during the COVID-19 pandemic except for emergency dental care was recommended. It is documented that health-seeking behaviors change during pandemics. The objective of this study was to examine social determinants associated with decisions to seek dental care in Saudi Arabia during the COVID-19 pandemic. Methods A total of 4372 participants were invited to this cross-sectional web-based survey distributed from April 21 to June 20, 2020. The survey included a list of emergency, urgent, and routine dental procedures. Participants were asked if they would seek dental care for these conditions during the pandemic, and what pain severity would make them seek dental treatment. Logistic regression models were performed for predicting variables that explain the decision to go or not to go to the dental clinic during the pandemic for each dental condition. Results A total of 3443 responded to this survey. The emergency dental situation participants were most willing to go to the dental clinic for was trauma involving facial bones compromising the airway (94.5%). Only 65.8% were willing to seek care for facial cellulitis compromising the airway. On average 35.2% reported seeking teleconsultation as the first step. Eighteen percent of participants were still willing to go to the dental clinic during the pandemic for routine dental procedures. Multiple logistic regression showed that females (Odds Ratio (OR): 1.6, OR 95% CI 1.3, 1.9), people who had never visited a dentist (OR: 1.8, OR 95% CI 1.3, 2.5), and people living in metropolitan regions (OR: 1.8, OR 95%: 1.4, 2.3) had higher odds for not seeking emergency dental care during this pandemic. The pain threshold for seeking dental care during the pandemic was 7 out of 10. Female, those who never visited a dentist, and those from urban regions reported higher pain threshold before seeking dental care (P value < 0.001). Conclusion Social disparities were found in emergency dental care seeking decision-making in Saudi Arabia during the COVID-19 pandemic. It was alarming that some people were afraid to seek dental care for life-threatening dental emergencies as cellulitis during this pandemic. This reflects the importance of increasing public health awareness and governmental regulations.